Content Vol. 42 No. 1 (2021) - Editorial, Coordinador (Revista Mexicana de Ingenieria Biomedica, 2021)
E-book edition of the volume 42, number 1, year 2021, of the Revista Mexicana de Ingeniería Biomédica. In this issue: Saliva analysis using FTIR spectroscopy to detect possible SARS-CoV-2 COVID-19) virus carriers The Impact of Staying at Home on Controlling the Spread of COVID -19: Strategy of Control A Method for Evaluating the Risk of Exposure to COVID-19 by Using Location Data ANOVA to Compare Three Methods to Track COVID-19 in Nine Countries Implementation and Technical Testing of a Robot for Future Use in Patients Care (Covid-19)